DIURNAL ACTIVITY OF CRESTED SERPENT-EAGLE (Spilornis cheela) IN PUSAT SUAKA SATWA ELANG JAWA - Ratu Dhania, Rania; Istiana, Rita; Zufitrianto, Hafidz; Supratman, Lilis (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Human activity such a deforestation, the extent of hunting and illegal trade of pets nowadays makes Crested Serpent-eagle’s population in its natural habitat is threatened. To overcome the problem, a rehabilitation is needed to keep its sustainability. Diurnal activity observastion is important in the rehabilitation process, because the result can be the standard for the eagle to completing a rehabilitation process and become a determining factor whether the eagle can move to the next rehabilitation stage and whether the animal can be released or not. Pusat Suaka Satwa Elang Jawa (PSSEJ) is one of rehabilitation centres specially established for mountain eagles which conduct eagles’ rehabilitation and release.This research aims at observing the diurnal activities of Crested Serpent-eagle which are in different rehabilitation stages. The observation was conducted during 10 days in September-October 2021 from 08.00 a.m until 04.0.00 p.m. The method used in this research was ad libitum sampling and focal animal sampling in PSSEJ quarantine and training cage. Based on the observation, it is concluded that there were three categories of Crested Serpent-eagles’ activity observed in quarantine cage and training cage. These activities include perching activities, moving activities and hunting activities. Each activity in each cage has a different percentage, but perching activity has the largest presentation in both cages, namely 92.11% in quarantine cages and 81.79% in training cages. This difference is caused by the rehabilitation stages which has been passed by the eagles, the size of the cage, and the environment condition Key words: Crested Serpent-eagle, Diurnal Activity, Rehabilitation